Simulation of irradiation-based processing system for natural rubber vulcanization - Kosaentor K. (2017)
© 2017 Trans Tech Publications, Switzerland. Natural rubber is an important export product of Thailand, which presently contributes about 40% of global production and export. In order to make the natural rubber latex to be durable material, the proper vulcanization process is needed. In typical vulcanization process, chemical substances are added to improve the rubber properties. This may cause some problems e.g. toxicity, blooming effects and unpresented smell due to the additive substances. Vulcanization using an accelerated electron beam does not need to add possibly toxic chemical compounds, especially sulfur. Thus, it was proved to be an alternative method for high quality natural rubber vulcanization. This paper presents about simulation of electron beam irradiation for natural rubber vulcanization with variable electron beam energy and current of 0.5-4 MeV and 10-100 mA, respectively. These ranges of the electron beam energy and current will give adjustable absorb dose, which is the most important parameter for electron beam processing. The absorb energy and its distribution in the natural rubber latex are simulated by using a Monte Carlo method program, GEometry ANd Tracking 4 (GEANT4), with the aim to find the optimal conditions of electron beam properties for sufficient natural rubber vulcanization. Study results of the energy distribution for electron beam penetration in the natural rubber latex are presented and discussed in this paper.